Effect of the Duration of Intraretinal or Subretinal Fluid on the Response to Treatment in Undertreated Age-Related Macular Degeneration - Izumi Yoshida; Masashi Sakamoto; Asao Sakai; Takatoshi Maeno (Journal of Ophthalmology)
We investigated the association between the duration of intraretinal fluid (IRF) or subretinal fluid (SRF) and the response to antivascular endothelial growth factor injection in patients with undertreated age-related macular degeneration (ARMD). The Ethics Committee of Toho University Sakura Medical Center approved this study (no. S18030). Eighty eyes of ARMD patients with VA ≤20/100 were retrospectively assessed. Each injection’s efficacy was classified, and the fluid accumulation prior to each injection was evaluated. The effect changes following to accumulated IRF, SRF, the longest persistent IRF period (≥10 months), and their determining factors were evaluated. Throughout observation, acquired refractoriness was rarely associated with increased accumulation of IRF or SRF. The injection span had a tendency to be short, and the polypoidal choroidal vasculopathy and occult choroidal neovasculopathy (CNV) proportions had a tendency to be higher among patients with diminished effects than among those with maintained effects. VA differed significantly with continuous IRF duration, but not with accumulated fluid. The diminishing effect of injections during long-standing IRF was rarely associated with undertreatment. The mechanism underlying acquired refractoriness remains unknown; the effect change demonstrated various patterns, including diminished and improved responses. The longest continuous IRF duration was associated with VA decline. Shortening the duration of continuous IRF may be necessary.